The Sex-Dependent Role of Myostatin Signaling in Contractures Following Neonatal Brachial Plexus Injury: 2022 POSNA Annual Meeting – Best Basic Science Research Paper - Marianne E. Emmert; Qingnian Goh; Kritton Shay-Winkler; Parul Aggarwal; Roger Cornwall (Journal of the Pediatric Orthopaedic Society of North America, 2022)
Purpose: Neonatal brachial plexus injury (NBPI) causes disabling and incurable muscle contractures, arising from impaired longitudinal growth of denervated muscles. This growth impairment is caused by dysregulation of muscle proteostasis characterized by increased proteasome-mediated protein degradation. Myostatin (MSTN), a secreted growth differentiation factor and prominent muscle-specific negative regulator of proteostasis, drives muscle protein degradation. MSTN signaling is thus a possible pathway through which denervation impairs muscle growth and a potential muscle-specific molecular target for preventing contractures. This study uses pharmacologic inhibition of MSTN signaling in a mouse model of NBPI to test the hypothesis that NBPI induces contractures through MSTN-dependent impairment of longitudinal muscle growth. Methods: Unilateral NBPI was generated in postnatal day (P)5 mice. Mice were treated weekly with Dulbecco’s phosphate-buffered saline (DPBS) or ACVR2B-Fc, a soluble inhibitory decoy receptor for MSTN, starting at P4. Mice were sacrificed at P33, whereupon elbow and shoulder range of motion were measured to assess contractures. Brachialis muscles were prepared for microCT assessment of cross-sectional area (CSA) and volume, then processed for sarcomere length measurement as a readout of longitudinal muscle growth. Total protein content in biceps was assessed via Bradford assay. Protein degradation in triceps was quantified via 20S proteasome β1 subunit activity assay. Results: In female mice, myostatin inhibition with ACVR2B-Fc enhanced muscle weight and total protein content of denervated biceps (Figure 1), increased cross-sectional and volumetric growth of denervated brachialis (Figure 2), preserved longitudinal growth in denervated brachialis (Figure 3), and reduced elbow and shoulder contracture severity in the denervated limbs (Figure 4). Analysis of protein dynamics demonstrates the improvements in female denervated muscles were associated with a reduction in proteasome β1 subunit activity (Figure 5). However, no such improvements in denervated muscles occurred in male mice with ACVR2B-Fc. Conversely, myostatin inhibition increased muscle weight, CSA, volume, and total protein content of the normally innervated, contralateral control muscles in both male and female mice (Figures 1 and 2). Conclusion: Our findings reveal MSTN as a driver of impaired muscle growth and contracture formation in female but not male mice. This sex dimorphism lies in the pathophysiology of denervation-induced contractures rather than drug pharmacodynamics, given the sex-independent effects of MSTN inhibition on normally innervated muscle. Future studies must rigorously interrogate the contributions of sex in contracture pathophysiology. Significance: Our discovery identifies MSTN as a signaling target for modulating contractures in females and highlights the overlooked role of sex in the pathophysiology of acquired neuromuscular disorders. Level of Evidence: Not Applicable FDA: The FDA has not cleared the following pharmaceuticals and/or medical devices for the use described in this presentation.